Proceedings of the Third International Afro-European Conference for Industrial Advancement - AECIA 2016 - Abraham, Ajith; Haqiq, Abdelkrim; Ella Hassanien, Aboul; Snasel, Vaclav; Alimi, Adel M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The Afro-European Conference for Industrial Advancement (AECIA) brought together the foremost experts and excellent young researchers from Africa, Europe and the rest of the world to disseminate the latest results from various fields of engineering, information and communication technologies. This volume gathers the carefully selected papers from the third installment of the AECIA, which was held in Marrakech, Morocco from November 21 to 23, 2016. The papers address important topics like Automation Systems, Intelligent Techniques and Algorithms, Information and Communication Technology (ICT) Applications in Engineering, Control, Optimization and Processing, as well as manufacturing-related topics. As such, it offers a valuable reference guide for researchers, students and practitioners in the fields of computer science and engineering.
Integrated Autopilot Complex System Proposal for Aircraft Model Application.- Synthesis and Implementation of Timed Distributed Supervisory Controller: Application to an Automated Manufacturing System.- A new fuzzy clustering algorithm to enhance lifetime of Wireless Sensor Networks -- SAM: Scalable Addressing Mechanism for Structured P2P Networks.- A Novel Ant Colony Optimization Based Cryptanalysis of Substitution Cipher.- Statistical modeling for improvement of numerical-model-based solar radiation forecasts.- A two-stage Feature Extraction Approach for ECG signals -- Contribution on character modelling for handwritten Arabic text recognition.
Keywords: Computational intelligence; Artificial intelligence; Control engineering; Computational Intelligence; Artificial Intelligence; Control and Systems Theory